Wettability of two different artificial saliva substitutes on injection moulded heat polymerized acrylic resin and CAD-CAM acrylic resin: an in vitro study. - Quraish Lal; Aamir Godil; Mosin Shaikh; Smita Musani; Ramandeep Dugal; Ajinkya Kirad (University Library System, University of Pittsburgh, 2023)
Aim: The purpose of this in vitro study was to evaluate the wettability of two different artificial saliva substitutes on injection moulded heat-polymerized acrylic resin and CAD-CAM acrylic resin and to compare these properties with natural saliva and distilled water. Materials and method: Forty heat polymerized (injection moulded) acrylic resin specimens and forty CAD-CAM acrylic resin specimens were fabricated with each specimen measuring 10x10x2mm. Four groups of liquids namely distilled water, Wet mouth™, Mouth Kote™ and human saliva were used. A contact angle goniometer was used to measure the contact angles. Two contact angle readings were obtained on the right side and on the left side of the test specimen. The observations were recorded and a mean of the two readings was calculated. The same procedure was repeated for all specimens (heat cure resin and CAD-CAM) with all the four test groups of liquids. Results: Contact angle measurements were significantly higher in Wet mouth™ and Mouth Kote™ solution of heat cure resin group compared to the CAD-CAM group (p-value<0.05 for both). Mouth Kote™ had lower mean contact angle (62.63 ± 4.59) than Wet mouth™ (77.46 ± 9.16) on CAD/CAM denture base resin. Mouth Kote also had lower mean contact angle (70.80 ± 4.79) than Wet mouth™ (97.77 ± 7.79) on injection moulded denture base resin. Conclusion: Mouth kote had better wettability than wet mouth on both CAD-CAM and injection moulded acrylic resin. Both the saliva substitutes had better wettability on CAD-CAM than on injection moulded acrylic resin.